Levels of Parasitism by Xenos oxyodontes (Strepsiptera, Stylopidae) among Adult Hornets and Its Voltinism in the Host Vespa analis (Hymenoptera, Vespidae) - Shun'ichi Makino (Sociobiology)
Stylopized adults of Vespa analis in collected nests and bait-trapped samples were examined to learn the intensity of parasitism and the life cycle of the parasite Xenos oxyodontes. Of the 48 nests collected between June and October in central Japan, 60% contained stylopized adults, with 8.2% of the total intranidal adult population stylopized. Stylopization rates varied by sex and caste; 7.3% in workers, 12.3% in males, and 1.7% in new queens. The overall sex ratio (male ratio) of the parasite was 0.76 within adult hornets, consistently male-biased across both the month of collection and the sex of the host. Stylopized adults occurred even in nests collected in October, toward the end of the nesting season. Considering the developmental periods of both the host and the parasite, such individuals of X. oxyodontes that occurred in the late-season nests likely belonged to the second generation, rather than to the first generation (descendants of overwintered females). Adults of V. analis bait-trapped between May and September consistently included hornets infested with X. oxyodontes females carrying first instar larvae, indicating that parasite infection occurs during this period. Female parasites found on workers produced in the current year were observed to carry first instar larvae from August onwards. This would be impossible if X. oxyodontes were univoltine and if newly emerged females always overwintered without releasing larvae within the same year, strongly supporting the hypothesis of bivoltine life cycle of X. oxyodontes parasitizing in the study region.